A Comprehensive Review of Prominent Biases and Other Factors Influencing Retail Investors’ Decision-Making - Singh, Saurabh; Bharti, Ipsa; Maurya, Preeti (Indian Journal of Finance, 2025)
Purpose : In the modern investment era, the emerging field of behavioral finance seems to have challenged the rational decision-making assumption of finance. The study focused on highlighting and consolidating the biases and other prominent factors that influence the decision-making of retail investors’ investments. Methodology : A systematic literature review (SLR) followed the PRISMA 2020 guidelines. A total of 134 articles indexed in the SCOPUS database from 2007 to 2025 were retrieved, out of which 47 were systematically reviewed. A bibliometric analysis was employed to explore the subject’s research landscape. Findings : Through the in-depth analysis, various behavioral biases and other prominent factors that influence the decision-making of retail investors were observed and consolidated. Furthermore, the intellectual research structure identified the underlying themes and collaborative patterns within the behavioral finance domain. Implications : This research offered insights into behavioral biases and other factors that shape the decision-making of retail investors, enhancing both academic and practical understanding. The role of financial literacy was highlighted, and financial institutions were urged to address hidden biases and promote rational investment decision-making. Originality : Most studies emphasized behavioral biases. Our study not only shed light on the biases but also identified other factors that affected the decision-making of retail investors.